2005
DOI: 10.1037/0096-1523.31.2.235
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-Object Tracking Is Based on Scene, Not Retinal, Coordinates.

Abstract: This study tested whether multiple-object tracking-the ability to visually index objects on the basis of their spatiotemporal history-is scene based or image based. Initial experiments showed equivalent tracking accuracy for objects in 2-D and 3-D motion. Subsequent experiments manipulated the speeds of objects independent of the speed of the scene as a whole. Results showed that tracking accuracy was influenced by object speed but not by scene speed. This held true whether the scene underwent translation, zoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
73
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(89 citation statements)
references
References 17 publications
16
73
0
Order By: Relevance
“…This may also be the case in the present experiments. Target losses are also more likely as the speed of the objects increases (our Experiment 3; Liu et al, 2005). Our results show that increases in speed also increase the attentional demands, which suggest that attention may be important for keeping an up to date representation of target locations.…”
Section: Using Dual-task Techniques To Assess Multiple-object Trackingmentioning
confidence: 55%
See 2 more Smart Citations
“…This may also be the case in the present experiments. Target losses are also more likely as the speed of the objects increases (our Experiment 3; Liu et al, 2005). Our results show that increases in speed also increase the attentional demands, which suggest that attention may be important for keeping an up to date representation of target locations.…”
Section: Using Dual-task Techniques To Assess Multiple-object Trackingmentioning
confidence: 55%
“…As the speed of objects increase, the probability that the model will lose the targets also increases because targets move too far from the predicted location to be differentiated reliably from distractors. In practice, Liu et al (2005) have shown that participants do indeed produce more errors in tracking when the speed of objects in a display is increased from 1°/s to 6°/s. Though sensitivity to speed is an attribute of serial mechanisms, it would also be an attribute of parallel mechanisms with limited spatial or temporal capacity.…”
Section: What Might Increase the Attentional Demands Of Tracking?mentioning
confidence: 99%
See 1 more Smart Citation
“…In conditions with objects visible throughout the entire trial, we expected lower visual tracking performance with abrupt viewpoint changes, as compared with the conditions with smooth and without viewpoint changes (Huff et al, 2009;Liu et al, 2005). In conditions without viewpoint changes, we expected slightly impaired MOT performance if the objects were temporarily invisible (Keane & Pylyshyn, 2006).…”
Section: Experimental Overviewmentioning
confidence: 90%
“…Recently, however, MOT was examined with scenes in motion. Liu et al (2005) showed that smooth scene motion-such as rotation, translation, and zoom-did not impair tracking performance. Continuous visual information about scene motion was sufficient to establish correspondence between targets from one moment to the next.…”
mentioning
confidence: 99%